2011
DOI: 10.1097/md.0b013e318207231e
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis of the Gastrointestinal Tract in Chronic Periaortitis

Abstract: The term "chronic periaortitis" (CP), proposed by Mitchinson in 1984, comprises 3 main entities: idiopathic retroperitoneal fibrosis (IRF), inflammatory abdominal aortic aneurysms (IAAAs), and perianeurysmal retroperitoneal fibrosis (PRF).The presence of constitutional symptoms, high acute-phase reactants, positive autoantibodies, and associated autoimmune diseases suggests a systemic inflammatory process. Histopathologic findings show vasculitis with fibrinoid necrosis involving the aortic vasa vasorum as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…The periaortic tissue can extend to the mesenteric and celiac arteries, causing stenosis and ischemic complications resembling mesenteric vasculitis. 24 Up to one-third of patients with abdominal RPF also have thoracic aorta involvement, most of them presenting with thoracic aorta aneurysm, the progression of which must also be carefully monitored. 7 Laboratory Findings Acute-phase reactants such as erythrocyte sedimentation rate and C-reactive protein levels are increased in the majority of patients at presentation and are routinely used to monitor disease activity.…”
Section: Clinical Manifestations and Laboratory Findingsmentioning
confidence: 99%
“…The periaortic tissue can extend to the mesenteric and celiac arteries, causing stenosis and ischemic complications resembling mesenteric vasculitis. 24 Up to one-third of patients with abdominal RPF also have thoracic aorta involvement, most of them presenting with thoracic aorta aneurysm, the progression of which must also be carefully monitored. 7 Laboratory Findings Acute-phase reactants such as erythrocyte sedimentation rate and C-reactive protein levels are increased in the majority of patients at presentation and are routinely used to monitor disease activity.…”
Section: Clinical Manifestations and Laboratory Findingsmentioning
confidence: 99%
“…[17][18][19] In a study of five patients with concomitant gastrointestinal vasculitis and chronic periaortitis, Salvarani et al found that histological data and imaging indicate the possibility of chronic periaortitis and its separate disease entities as a type of large-vessel vasculitis. 20 More recently, researchers have found an association between RPF and IgG4-related systemic disease. In a review of 14 published cases of IgG4-related RPF, Stone found that all of the cases identified as IgG4-related, based on a serology, were male, which confirmed prior evidence of male predominance in IgG4-related systemic diseases.…”
Section: Pathologymentioning
confidence: 99%
“…8,24,39,55,62,63 Gastrointestinal involvement is usually associated with a worse prognosis in these forms of SV. 46,57,62 Abdominal territories may rarely be the site of a focal singleorgan vasculitis (SOV).…”
Section: Introductionmentioning
confidence: 99%